2023
DOI: 10.3390/plants12071462
|View full text |Cite
|
Sign up to set email alerts
|

How Does Changing Environment Influence Plant Seed Movements as Populations of Dispersal Vectors Decline?

Abstract: Plants differ widely in their ability to find tolerable climatic ranges through seed dispersal, depending on their life-history traits and habitat characteristics. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic review on seed dispersal mechanisms was conducted to elucidate plant seed movements amid changing environments. Here, the highest relative count of studies was found in Spain (16.47%), followed by Brazil (14.12%), and the USA (14.12%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Dispersal mechanisms include wind, water, animals, or human activities such as transportation and trade (Fig. 2; Hernandez, Naeem & Zaman, 2023). For example, a single Eurasian watermilfoil Myriophyllum spicatum plant can produce thousands of seeds, which are easily transported by water currents, waterfowl, or human activities, allowing it to colonise new habitats rapidly (Petruzzella et al ., 2018).…”
Section: General Concept Of Invasivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Dispersal mechanisms include wind, water, animals, or human activities such as transportation and trade (Fig. 2; Hernandez, Naeem & Zaman, 2023). For example, a single Eurasian watermilfoil Myriophyllum spicatum plant can produce thousands of seeds, which are easily transported by water currents, waterfowl, or human activities, allowing it to colonise new habitats rapidly (Petruzzella et al ., 2018).…”
Section: General Concept Of Invasivenessmentioning
confidence: 99%
“…The dandelion ( Taraxacum officinale ) produces numerous lightweight seeds that are easily carried by the wind, facilitating its widespread distribution (DiTomaso & Barney, 2012). Dispersal by animal vectors may also be involved, for example Sturnus vulgaris aids in the spread of Rosa multiflora by consuming and dispersing the seeds (Hernandez et al ., 2023). Berihun et al .…”
Section: General Concept Of Invasivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, dispersal evolves even in the simplest systems with homogenous environments (Hamilton & May, 1977 ) and is especially important for sessile organisms, such as plants, that have limited opportunities during their life cycle for movement (Beckman & Sullivan, 2023 ). In heterogeneous habitats, environmental conditions are an important driver of plant dispersal ability, which can manifest locally through differences in physical properties of the environment (e.g., soil depth, habitat structure, fragmentation) as well as in a more broad‐scale way through the climate in the year of reproduction (Hernandez et al., 2023 ). When the impact of multiple environmental factors are considered synergistically on dispersal in theoretical studies, strong effects on plant movement are often found, with factors like fragmentation and climate change both slowing dispersal (Renton et al., 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of current climatic trends for forest vegetation vary greatly depending on a number of factors, such as local conditions (moisture availability, orography, etc. ), ecophysiological characteristics of species, individual genotypes, and even tree age [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Even the direction of impact is ambiguous: in some regions, there is a strong negative or even catastrophic effect; in others, stable forest growth or even positive changes can be observed [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%